NILAI-NILAI RELIGIUS PADA LIRIK LAGU KETIKA TANGAN DAN KAKI BERKATA KARYA TAUFIQ ISMAIL DAN APLIKASINYA PADA MATA KULIAH PENULISAN KREATIF DI PRODI PBSI, FKIP, UNISSULA - Meilan Arsanti (TRANSFORMATIKA, 2017)
This descriptive study was conducted to describe religious values in lyrics of Taufiq Ismail’s song “Ketika Tangan dan Kaki Berkata” and its usage in a learning because religious value, as one of 18 character values mentioned by the Ministry of National Education, had not been discussed further in studies. The song was created by Taufiq Ismail with Surah Yasin verse 65 as the inspiration. The research method used was descriptive analytic method including 4 stages, namely 1) grouping data, 2) studying lyrics, 3) interpreting song lyrics, and 4) drawing conclusion. Based on the analysis result, it could be concluded that religious values contained in “Ketika Tangan dan Kaki Berkata” lyrics were shiddiq, amanah, fathanah, and tabligh. These religious values were then applied to Creative Writing (Penulisan Kreatif) course in Indonesian Language and Literature Education Department, Sultan Agung Islamic University. In the next research, results of this study analysis will be developed into Creative Writing course materials. Eventually, this study did not only analyze the religious values in the song lyrics, but also applied them in the lecture and used them as islamic-based teaching materials.Keywords: religious values, song lyrics, creative writing